A case report of isolated rheumatic tricuspid regurgitation and pericarditis. Issue 1 (February 2021) - Alhadramy, Osama
الملخص: الحمى الروماتيزمية هي متلازمة معقدة، حيث يشكل جسم الإنسان أجساما مضادة لعدوى المكورات العقدية الانحلالية من النوع "بيتا"، التي تؤدي إلى التهابات في أعضاء الجسم المختلفة. تؤثر التهابات الصمامات الناتجة عن الحمى الروماتيزمية في الغالب على الصمام الميترالي وبدرجة أقل على الصمام الأبهري. ويعتبر مرض الصمام ثلاثي الشرفات الروماتزمي المنفرد والتهاب التامور نادرين للغاية ولم يوصفا بشكل جيد في إرشادات الحمى الروماتيزمية. توضح حالتنا نتائج تخطيط صدى القلب لالتهاب الصمام ثلاثي الشرفات الناتج عن الحمى الروماتيزمية ويصف تغيرات تخطيط القلب الكهربائي في التهاب التامور. عند الفحص، وجد أن المريض لديه نفخة ارتجاع الصمام ثلاثي الشرفات. وكشفت الفحوصات المختبرية ارتفاع معدل ترسيب الكريات الحمراء، وبروتين سي التفاعلي ومضادات الترتيبتولين وأيضا معدل الأجسام المضادة لبروتين الستريبتوليسين. كما أظهر تخطيط صدى القلب، ارتجاع الصمام ثلاثي الشرفات مع زيادة في سمك أطرافه بشكل ملحوظ، في حين كان الصمام الميترالي والأبهري طبيعيان في الهيكل والوظيفة. تم تشخيص المريض بالحمى الروماتيزمية وأعطي مضادا حيويا وجرعة عالية من الأسبيرين. وأدى ذلك إلى ذهاب ألم الصدر. تسلط حالتنا الضوء على حقيقة أن نتائج الفحوصات السريرية والمختبرية لارتجاع الصمام ثلاثي الشرفات الروماتيزمية تشبه ارتجاع الصمام الميترالي الروماتزمي. وبالمثل، فإن التهاب التامور الروماتزمي مماثل للأنواع أخرى، ويمكن أن يستجيب لجرعات عالية من الأسبرين. وأخيرا، ينبغي أن يكون الأطباء على دراية بالمضاعفات الشائعة والنادرة للحمى الروماتيزمية لأن المبادئ التوجيهية الجديدة وضعت منطقتنا بين البلدان المعرضة للخطر. Abstract: Rheumatic fever (RF) is a complex syndrome in which the human body develops antibodies against β-haemolytic streptococcus, and triggers inflammation in various organs. RF valvulitis mostly affects the mitral valve (MV) and, to a lesser extent, the aortic valve (AV). Isolated rheumatic tricuspid valve (TV) disease and pericarditis is extremely rare and is not well described in the RF guidelines. The current case demonstrates the echocardiographic findings of TV valvulitis of RF and describes the presentation and electrocardiogram (ECG) changes in pericarditis. We present the case of a 16-year-old male patient who developed upper respiratory tract infection followed by typical pericarditis chest pain. The patient had no history of joint pain or swelling, but was found to have a tricuspid regurgitation (TR) murmur upon examination. Laboratory investigations revealed an elevated erythrocyte sedimentation rate, and elevated C-reactive protein and antistreptolysin O titres. ECG showed a wide-spread 1.5 mm upward concave ST-segment elevation. In echocardiography, the TV opened well with markedly thickened leaflets and severe TR, while the MV and AV were normal in both structure and function. The diagnosis of RF was established and treatment with high-dose aspirin and antibiotics was initiated. The treatment led to resolution of the chest pain. Our case highlights that the physical and lab findings of rheumatic TR are similar to those of rheumatic mitral regurgitation, with the exception of a high-velocity jet. Similarly, the presentations of rheumatic pericarditis are similar to other types and may also respond to high-dose aspirin. Finally, physicians should be familiar with both the common and rare complications of RF because the guidelines have placed Middle East region among the high-risk countries.